A superadditive solution - Diethard Pallaschke; Joachim Rosenmüller (Bielefeld University, Institute of Mathematical Economics (IMW), 2004)
We present a superadditive bargaining solution defined on a class of polytopes in Rⁿ. The solution generalizes the superadditive solution exhibited by MASCHLER and PERLES.
urn:nbn:de:hbz:361-6252
Keywords: 330